ORGANIZATIONAL CULTURE PATHWAY LINKING LEADERSHIP AND PERFORMANCE AMONG HEALTHCARE WORKERS IN MALAYSIAN PUBLIC HOSPITALS - Tharmarajah Nagalingam; Md Mizanur Rahman (Veredas do Direito, 2026)
In hospitals around the globe, there exists a tripartite culture of leadership and performance in their daily operations. Job performance among healthcare workers often depends on hospital organizational culture, psychosocial conditions, and leadership. This study examined how organizational culture mediates the relationship between transformational leadership and job performance in public hospitals in Malaysia. A cross-sectional survey was conducted among 1,187 doctors, nurses, and medical assistants from 11 public hospitals in Malaysia. A validated self-administered questionnaire was used to assess organizational culture, transformational leadership, and job performance among doctors, nurses, and medical assistants in eleven (11) selected public hospitals in Malaysia. These data were collected and analyzed using hierarchical multiple linear regression and partial least squares structural equation modeling. These statistical methods were used to estimate the direct, indirect, and moderating effects on job performance among healthcare workers. Organizational culture, however, showed the strongest direct association with job performance (β = 0.987, p < .001). Transformational leadership was strongly associated with organizational culture (β = 0.869, p < .001) and had a large positive indirect effect on job performance via culture (β = 0.858, p < .001), despite a small negative direct effect (β = −0.224, p = .042). The model explained 64.6% of the variance in job performance. Therefore, Organizational culture is the primary proximal determinant of job performance and the key pathway to transformational leadership. Improving job performance in public hospitals in Malaysia should prioritize leadership development and culture-building.